Adaptação do indicador de salubridade ambiental para análise de empreendimentos do Programa de Arrendamento Residencial em Aracaju - SE - Buckley, Cristina Fernandes de Oliveira (2010)
Sustainable development must provide life quality to the population, including health and house sanitation. One of the means for evaluating the effects over the health of the environment is the Indicator of Environmental Health IEH, used by several authors after being adapted to its specific subject. Considering the Social Housing Program SHP great acceptation in Aracaju/SE and the location of most condos in areas of environmental protection, the indicator IEH/SHP is used in this research to evaluate the condos located in that town. This indicator is based upon the sub-indicators Water Supply, Sanitation, Solid Waste, Vector Control, Public Places, Housing Conditions, Housing Satisfaction and Efects over the Neighborhood. The six condos analyzed showed good conditions, except sanitation, vector control and public places in some of them.